2019
DOI: 10.1177/1071181319631409
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Trust During an Automated System Monitoring Task: Preliminary Results of an Effective Connectivity Study

Abstract: As autonomous systems become more prevalent and their inner workings become more opaque, we increasingly rely on trust to guide our interactions with them especially in complex or rapidly evolving situations. When our expectations of what automation is capable of do not match reality, the consequences can be sub-optimal to say the least. The degree to which our trust reflects actual capability is known as trust calibration. One of the approaches to studying this is neuroergonomics. By understanding the neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…They also report that this activation negatively correlates with human trust; an increase in activation suggests lower trust. Validation of this experiment was perfomed by Sanders et al (2019), who also observed increased activation of the region around FCz during unreliable conditions. All EEG studies that manipulated reliability report similar findings, where at least one of the locations Fz, F1, F2, FC1, FCz, FC2, C1, Cz, C2 are identified with identical activation direction (increased activity for lower trust).…”
Section: Activation Featuresmentioning
confidence: 85%
“…They also report that this activation negatively correlates with human trust; an increase in activation suggests lower trust. Validation of this experiment was perfomed by Sanders et al (2019), who also observed increased activation of the region around FCz during unreliable conditions. All EEG studies that manipulated reliability report similar findings, where at least one of the locations Fz, F1, F2, FC1, FCz, FC2, C1, Cz, C2 are identified with identical activation direction (increased activity for lower trust).…”
Section: Activation Featuresmentioning
confidence: 85%
“…Contemporary technology advances in automation, artificial intelligence (AI), and computational algorithms have created great benefits for human operators, as well as increases in adverse or unexpected consequences [1], [2], [3]. To ensure safe and seamless human-machine interaction (HMI), trust between humans and machines (in the form of AI or automated tools) has become a widely discussed topic over the past three decades [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…More specific and operational definitions of human-machine trust that has been widely accepted in the current human factors literature concern the perception of trust as: (i) "the extent to which a user is willing to act on the basis of the information, recommendations, actions, and decisions of a computer-based tool or decision aid" (p. 11 in [7], adapted from p. 1 in [9])) or (ii) "the attitude that an agent will help achieve an individual's goals in a situation characterized by uncertainty and vulnerability" (p. 6 in [10]). Here, it is worth noting that according to the second operational definition, trust is characterized as decision-making heuristic that machine operators use in situations that are too uncertain or changing rapidly [3], [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations